2020
DOI: 10.1101/2020.12.06.20244863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent Homology of Tumor CT Scans is Associated with Survival In Lung Cancer

Abstract: Radiomics, the objective study of non-visual features in clinical imaging, has been useful in informing decisions in clinical oncology. However, radiomics currently lacks the ability to characterize the overall structure of the data. This field may benefit by incorporating persistent homology, a popular new algorithm that analyzes whole data structure. We hypothesized that persistent homology could be applied to lung tumor scans and predict clinical variables. We obtained computed tomography lung scans (n = 56… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…TDA is a well-established data analytic technique for unbiased data-driven discovery–based phenotyping ( 7 ). TDA has proven to be a powerful tool, yielding critical insights in the prognostic phenotyping ( 8 ), cancer imaging biomarker stratification ( 9 ), disease classification using pathology biomarkers ( 10 ), and omics-based cancer phenotyping ( 11 ). Several publications have reported the use of TDA in the metabolomics field, for example, unbiased lipid phenotyping of lung epithelial lining fluid ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…TDA is a well-established data analytic technique for unbiased data-driven discovery–based phenotyping ( 7 ). TDA has proven to be a powerful tool, yielding critical insights in the prognostic phenotyping ( 8 ), cancer imaging biomarker stratification ( 9 ), disease classification using pathology biomarkers ( 10 ), and omics-based cancer phenotyping ( 11 ). Several publications have reported the use of TDA in the metabolomics field, for example, unbiased lipid phenotyping of lung epithelial lining fluid ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another natural extension would be to apply the SINATRA Pro pipeline to other data types used to study variation in 3D protein structures such as cryogenic electron microscopy (cryo-EM), nuclear magnetic resonance (NMR) ensembles, and X-ray crystallography (i.e., electron density) data. Previous work has already shown that topological characteristics computed on tumors from magnetic resonance images (MRIs) have the potential to be powerful predictors of survival times for patients with glioblastoma multiforme (GBM) [17,51] and other cancer subtypes [52][53][54]; however, it has also been noted that the efficacy of current topological summaries decreases when heterogeneity between two phenotypic classes is driven by minute differences [13]. For example, cryo-EM images can look quick similar even for two proteins harboring different mutations.…”
Section: Discussionmentioning
confidence: 99%
“…al., describing the co-occurrence of nuclear features in physical cell neighborhoods (Saito et al 2016). Recent interdisciplinary work has successfully extended different graph-based topological analyses to image derived point clouds and more recently to images themselves, including the use of cubical complexes to derive prognostic topological features from medical images (Lawson et al 2019;Hajij, Zamzmi, and Batayneh 2021;Somasundaram, Litzler, et al 2021;Somasundaram, Wadhwa, et al 2022).…”
Section: Introductionmentioning
confidence: 99%